Implementasi Pendidikan Kewirausahaan di Kelompok Bermain Arofah Kecamatan Siswodipuran Kabupaten Boyolali - Wahyuni, Tris; Haryati, Titik; Rasiman, Rasiman (PGRI Kota Semarang, 2024)
The aim of this research is to discuss 1) Character values ​​implemented in entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency, 2) Strategies in implementing entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency. Informants who were sources included school principals, teachers, student guardians and foundation administrators. The research method used is field research using qualitative methods. Interviews, observations, using data collection techniques. Checking the validity of the data is carried out through triangulation techniques. The data analysis technique was carried out by describing, analyzing and identifying the implementation of entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency. The description and analysis are based on findings, events, processes and results of implementing entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency. The results of the implementation of entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency include the character values ​​implemented in entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency in the quite good category. In terms of strategy in implementing entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency, it is in the quite good category. Based on these problems, it can be concluded that the implementation of entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency can be said to have implemented character values ​​in entrepreneurship education in the Arofah Playgroup, Siswodipuran District, Boyolali Regency, which include: 1) independent, 2) creative, 3) brave taking risks, 4) Action oriented, 5) leadership and 6) hard work. Strategies for implementing entrepreneurship education in the Arofah Play Group, Siswodipuran District, Boyolali Regency include: 1) Integrating it into all subjects, 2) Combining it with extracurricular activities, 3) Entrepreneurship education through self-development, 4) Changes in the Implementation of Entrepreneurship Learning from Learning Concepts/Theories Entrepreneurship Practices, 5) Integration in textbooks or materials, 6) Integration through school culture, and 7) Integration through local content